Aumentando la confianza en campañas de recaudación de fondos de los estudiantes de la Universidad Icesi a través de la web 3.0. (2022)
According to figures from the World Bank Group (2021), with the advent of the Covid-19 pandemic in 2020, about 100 million more people were added to extreme poverty. This can also be evidenced within Icesi University at Cali, Colombia, since for the period 2021-2 57.8% of the students enrolled for undergraduate programs were students with a low level of income. For this reason, there is constant evidence in the community of the use of fundraising campaigns in channels such as social networks and web platforms, for different purposes, mainly the economic one. These campaigns, however, are being affected by a lack of trust from the donors, so this project aims to address the problem from a design perspective and solve it through the use of web 3.0 technology.